Africa in the age of globalisation perceptions, misperceptions and realities - Shizha, Edward; Diallo, Lamine (International political economy of new regionalisms series, 2015)
The book provides up-to-date scholarly research on continental trends on various subjects and concerns of paramount importance to globalisation and development in Africa.